A cognitive approach to lie detection: a meta-analysis - Vrij, Aldert (Legal and criminological psychology, 2017)
Introduction. This article provides a meta-analysis of a new, cognitive approach to (non-)verbal lie detection. This cognitive lie detection approach consists of three techniques: (1) imposing cognitive load, (2) encouraging interviewees to say more, and (3) asking unexpected questions. Method. A meta-analysis was carried out on studies using the cognitive approach, 14 of which directly compared the cognitive approach to a standard approach. Results. The cognitive lie detection approach produced superior accuracy results in truth detection (67%), lie detection (67%), and total detection (truth and lie detection combined, 71%) compared to a traditional standard approach (truth detection: 57%; lie detection: 47%; total detection: 56%). Conclusions. Practitioners may find it useful to use a cognitive lie detection approach in their daily practice.